Efektivitas Penerapan Perangkat Perkuliahan Mikrobiologi Berbasis Kontekstual Terhadap Kemampuan Berpikir Tingkat Tinggi Mahasiwa Pendidikan Biologi Unimed - Hasruddin Hasruddin; Fauziyah Harahap; Mahmud Mahmud (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2018)
This study aims to determine the effectiveness of the application of lectures in the pattern of six task models (routine tasks, critical journal analysis, textbook critical analysis, idea engineering, mini research, and projects) on students' high-order thinking in microbiology lectures. This research was conducted by using exprient method. The research population is 7 classes with a total of 280 students. The sample is determined by cluster random sampling, the class of Dik A uses six task patterns in the contextual learning order as much as 36 people and the class of Dik C with the pattern of six tasks in the direct learning order as many as 35 people. Data were obtained by using pretest and postes in the form of an essay test. The analysis technique used t test at 5% significance level. The result of the research is found that Ho is rejected and Ha is accepted t calculated = 7.758 (p = 0.000), it means that pattern of six task model in contextual learning order is more effective used to influence student's high thinking skill in microbiology lecture at Biology Education Program FMIPA of Universitas Negeri Medan.